Reindeer on Prins Karls Forland, Svalbard - Gjertz, Ian (Polar Research, 1995)
Svalbard reindeer were exterminated on the island of Prins Karls Forland just after the turn of the last century. In July 1994, after a period of 90 years, reindeer were again observed on the island.